2007
DOI: 10.1007/s12072-007-9008-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for hepatitis C infection in rural north Vietnam

Abstract: Background In Vietnam, the prevalence of hepatitis C virus (HCV) infection among injecting drug users and patients with liver disease is known to be high, yet the magnitude of HCV in the general population, particularly in rural areas, has not been clearly estimated. A community-based study was used to determine the prevalence of HCV infection in a rural population of north Vietnam and explore risk factors associated with HCV acquisition. Method A community-based viral hepatitis seroprevalence study using a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
(32 reference statements)
2
43
2
2
Order By: Relevance
“…26 The prevalence in the study population was comparable to the HBV prevalence previously reported among the general population of Binh Dinh Province during 1998-2000 (10.6%), 27 Thai Nguyen province (8.8%) 12 and Quang Tri province (11.4%). 15 Nevertheless, the HBV prevalence from our study was lower than that the previous report among the general population in Thanh Hoa province (18.8%), 14 Thai Binh province (19.0%), 17 and Binh Thuan province (15.3%). 13 The lower prevalence rate observed in our study might be explained by the following reasons.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…26 The prevalence in the study population was comparable to the HBV prevalence previously reported among the general population of Binh Dinh Province during 1998-2000 (10.6%), 27 Thai Nguyen province (8.8%) 12 and Quang Tri province (11.4%). 15 Nevertheless, the HBV prevalence from our study was lower than that the previous report among the general population in Thanh Hoa province (18.8%), 14 Thai Binh province (19.0%), 17 and Binh Thuan province (15.3%). 13 The lower prevalence rate observed in our study might be explained by the following reasons.…”
Section: Discussioncontrasting
confidence: 67%
“…Meanwhile, the HCV prevalence based on positive antibody against HCV (anti-HCV) among the general population ranges from 0.35% to 2.2%. [17][18][19] The most common route of HBV transmission reported in Vietnam is mother to child transmission, 20 whereas unsafe injection is the main transmission mode for HCV. 21 However, no study has been conducted on the relationship between providing beauty treatments and viral hepatitis infection.…”
Section: Prevalence Of Hepatitis B Virus and Hepatitis C Virus Infectmentioning
confidence: 99%
“…Limited studies from Vietnam have identified geographically dependent risk factors that are also not commonly seen in Western countries: ventoused scarifications (also known as cupping, the practice of administering glass cups onto soft skin as part of a therapeutic procedure involving bloodletting) [29] and acupuncture were associated with the transmission of HCV in Ho Chi Minh City in Southern Vietnam, whereas a history of hospitalization and tattoos were identified as risk factors for HCV acquisition in two randomly selected rural districts in Northern Vietnam [15,30].…”
Section: Discussionmentioning
confidence: 99%
“…Among blood donors, patients with liver diseases, 5,6,8,9,11,27 and hospitalized nonliver disease patients, the prevalence was higher from the general population (Tables 1 and 2). 5,6,8,9,11,27 The most important risk factor was injecting drugs, as it relates to the transmission through sharing of needles and syringes. 17 In addition, repeated blood donation 6 and history of surgery, acupuncture, medical injections, and dental treatment were also reported risk factors for HCV infection in Vietnam.…”
Section: Overview-hepatitis B and C And Hiv Coinfection In Vietnammentioning
confidence: 98%
“…Moreover, 34.8% to 80% of patients with liver cancer can be attributable to HBV. 8,9,11,17,27,41 For the association between HCV and liver cancer, there are very limited data and only 1 study has reported that 14% of liver cancer was due to HCV infection. 17 Mathematical models estimate nationally that by 2013, the number of people with chronic HBV infection will reach its peak at 8.6 million cases and then decrease to 8 million by 2025, as a direct impact of the universal infant vaccination.…”
Section: Burden Of Viral Hepatitis and Liver Diseasesmentioning
confidence: 99%